2011
DOI: 10.1111/j.1365-246x.2011.05059.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pulverized granitoids in a shallow core along the San Andreas Fault, Littlerock, CA

Abstract: S U M M A R YWe present results on the composition, structure and particle size distribution (PSD) of pulverized and damaged granitic rocks in a 42-m-deep core adjacent to the San Andreas Fault near Littlerock, CA. The cored section is composed of pulverized granites and granodiorites, and is cut by numerous mesoscopic secondary shears. The analysis employs XRD, XRF, thin sections and semi-automated particle size analyser methods, including a novel calibration method. The mean particle size for the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Therefore, fractal dimensions can be reliable indicators of comminution processes [e.g., Monzawa and Otsuki, 2003;Keulen et al, 2007;Stünitz et al, 2010]. The particle size distributions of pulverized rocks in the SAF have been studied previously Wechsler et al, 2011]. However, the fractal characteristics, particularly the quantitative differences when compared with brittle fault rocks of other large fault zones, have not previously been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fractal dimensions can be reliable indicators of comminution processes [e.g., Monzawa and Otsuki, 2003;Keulen et al, 2007;Stünitz et al, 2010]. The particle size distributions of pulverized rocks in the SAF have been studied previously Wechsler et al, 2011]. However, the fractal characteristics, particularly the quantitative differences when compared with brittle fault rocks of other large fault zones, have not previously been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that other evidence of earthquake faulting can be preserved in fault rocks, such as fault gouge graphitization (Kuo et al, , ), pulverized rocks (Mitchell et al, ; Rempe et al, ; Wechsler et al, ), fault gouge with high magnetic susceptibility (Pei et al, ), injection veins formed under extreme transient stress (Lin et al, ; Rowe & Griffith, ), and fault gouge with angular fragments of varied sizes (Li et al, ). Large earthquakes caused by thrust faulting usually generate surface rupture zones accompanied by vertical displacements; therefore, fault rock deformation not only provides information about fault seismic activity and earthquake mechanisms but also yields insights into mountain uplift caused by seismic faulting.…”
Section: Introductionmentioning
confidence: 99%
“…An extreme example of off-fault damage is the pulverized rock located next to sections of some major strike-slip faults, for example the San Andreas Fault (DOR et al 2006a;WECHSLER et al 2011). They reflect the need to understand the damage processes in these areas, because they can provide important information on rupture propagation during an earthquake (DOR et al 2006a, b), on earthquake propagation velocity, and on the dynamic effects responsible for gouge formation (RECHES and DEWERS 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They reflect the need to understand the damage processes in these areas, because they can provide important information on rupture propagation during an earthquake (DOR et al 2006a, b), on earthquake propagation velocity, and on the dynamic effects responsible for gouge formation (RECHES and DEWERS 2005). They also help distinguish between damage related to fault processes and surfaceweathering (WECHSLER et al 2011).…”
Section: Introductionmentioning
confidence: 99%